IMPLEMENTASI APLIKASI MENU PEMESANAN DENGAN QR CODE PADA WARUNG KOPI MENGGUNAKAN METODE FCFS BERBASIS ANDROID - Veronika, Juwita; Putri Pratiwi, Mariska (LPPM Universitas Putera Batam, 2025)
In the current era, coffee shops have become popular destinations for people to unwind while enjoying a variety of food and beverages. Nevertheless, conventional manual ordering systems often result in lengthy queues and operational inefficiencies. To overcome these challenges, this research focuses on developing an Android-based menu ordering application that utilizes QR Code technology combined with the First Come First Serve (FCFS) method. The application aims to streamline the ordering process for customers without requiring staff assistance while enhancing overall workflow efficiency. By employing QR Code technology, customers can view the menu directly on their devices, place orders, and send them digitally to the system. The FCFS method ensures that orders are processed in the sequence they are received, thereby reducing errors in service prioritization. The application was developed using the Waterfall model of the Software Development Life Cycle (SDLC), which encompasses stages such as requirements analysis, design, implementation, and testing. Testing outcomes reveal that the application significantly improves ordering efficiency, decreases waiting times, and increases user satisfaction. By adopting this system, coffee shops can enhance service quality, optimize operations, and provide customers with a more seamless and enjoyable experience.